Evaluation of salt content in school meals - Viegas, C.A.C.L . (2015)
Objective High blood pressure is a major rick factor for cardiovascular disease, and it is closely associated with salt intake. Schools are considered ideal environments to promote health and proper eating habits. Therefore the objective of this study was to evaluate the amount of salt in meals served in school canteens and consumers' perceptions about salt. Methods Meals, including all the components (bread, soup, and main dish) were retrieved from school canteens. Salt was quantified by a portable salt meter. For food perception we constructed a questionnaire that was administered to high school students. Results A total of 798 food samples were analysed. Bread had the highest salt content with a mean of 1.35 g/100 g (SD=0.12). Salt in soups ranged from 0.72 g/100 g to 0.80 g/100 g (p=0.05) and, in main courses, from 0.71 g/100 to 0.97 g/100g (p=0.05). The salt content of school meals is high with a mean value of 2.83 to 3.82 g of salt per meal. Moreover, a high percentage of students consider meals neither salty nor bland, which shows they are used to the intensity/amount of salt consumed. Conclusion The salt content of school meals is high, ranging from 2 to 5 times more than the Recommended Dietary Allowances for children, clearly exceeding the needs for this population, which may pose a health risk. Healthy choices are only possible in environments where such choices are possible. Therefore, salt reduction strategies aimed at the food industry and catering services should be implemented, with children and young people targeted as a major priority.